Seasonal circulation and water exchange with the Southern South China Sea of the Gulf of Thailand - Youting Wu; Changshui Xia; Fangli Qiao; Jingsong Guo; Dapeng Qu; Yue Fang (Continental Shelf Research, 2026)

Orally engineered liver-targeted garlic exosome-like nanovesicles for astaxanthin precise delivery against alcoholic liver disease in mice - Qinglin Qu; Fan Liu; Huajing Gao; Xiangrui Kong; Xue Gao; Yukun Song; Mingqian Tan; Yannan Chen; Dapeng Li; Xintong Tan (Food Research International, 2026)

Electrochemical aptamer sensor based on nanocomposites composite material for rapid on-site detection of enrofloxacin in aquaculture - Bo Long; Qi Liu; Yizhuan Li; Qiongqiong Xing; Chuxiong Lan; Rui You; Liying Deng; Fangfang Qu; Meng An; Yingchun Fu; Shenghang Zhang; Dapeng Ye; et al. (Chemical Engineering Journal, 2026)

Copper-based drugs inhibit infectious bronchitis virus (IBV) in vitro and in vivo - Lisen Lin; Jiaqi Li; Chao Shang; Dapeng Li; Mingzhe Sun; Gaojie Song; Guangbo Qu; Xiao Li; Ran Zhu; Cuiling Zhang; Qinghao He; Guibin Jiang (Veterinary Microbiology, 2026)

Inulin alleviates high-salt diet-induced cognitive impairment: A study on multi-target regulation mechanisms via the gut-brain axis - Huajing Gao; Qifang Guo; Qinglin Qu; Jiaqi Liu; Fan Yang; Xue Gao; Peihua Li; Yanquan Mu; Dapeng Li; Xintong Tan (Food Research International, 2026)

Modeling assessment of carrying capacities of kelp and bivalve polyculture bay based on ecological model - Xuehai Liu; Xuelei Zhang; Shang Chen; Xinming Pu; Dapeng Qu; Zongjun Xu (Ecological Modelling, 2025)

Eukaryotic expression and characterization of two α1,2-fucosyltransferase genes in the histo-blood group antigens synthesis pathway of the Pacific oyster (Crassostrea gigas) - Junxia Hu; Meng Qu; Weiran Zhang; Binbin Gui; Yanhua Jiang; Lin Yao; Shixin Wang; Dapeng Wang (Glycoconjugate Journal, 2025)

Plant-derived exosomes as bioactive compounds carriers for precision nutrition - Yannan Chen; Yuanyuan Liu; Huajing Gao; Qinglin Qu; Ziyue Xu; Minghan Zhang; Dapeng Li; Mingqian Tan (Trends in Food Science & Technology, 2025)

Recent advances in nanomaterial biosensors for the detection of antibiotics to ensure food safety - Bo Long; Qian Zhang; Lintong Zhang; Qiongqiong Xing; Qi Liu; Liying Deng; Fangfang Qu; Rui You; Xuan Wei; Dapeng Ye; Zhanhui Yuan (Chemical Engineering Journal, 2025)

Calibration of High-Frequency Reflectivity of Sediments with Different Grain Sizes Using HF-SSBP - Shuai Xiong; Xinghui Cao; Zhiguo Qu; Dapeng Zou; Huancheng Zhen; Tong Zeng (Journal of Marine Science and Engineering, 2025)
Accurate and efficient acquisition of the acoustic reflection properties of sediments with different grain sizes is key for sediment substrate classification and the construction of seafloor acoustic scattering models. To accurately measure surface sediments on the seafloor, an in-depth investigation of the acoustic properties of sediments with different grain sizes at different measurement distances is an indispensable prerequisite. While previous studies have extensively explored the acoustic reflection properties of sediments in mid- and low-frequency bands (e.g., 6–85 kHz), research on high-frequency reflectivity (95–125 kHz) remains limited. Existing equipment often suffers from large beam angles (e.g., >10°), leading to challenges in standardising laboratory measurements. To this end, we developed a technique using a high-frequency submersible sub-bottom profiler (HF-SSBP) to measure the high-frequency reflection intensity of homogeneous sediments screened by grain size. To ensure stable measurements of the high-frequency reflection intensity, we conducted experiments using standard acrylic plates. This demonstrates the dependability of the HF-SSBP and determines the absolute measurement error of the HF-SSBP. Variations in radiofrequency reflection intensity across different sediment types with different grain sizes in a frequency range of 95–125 kHz were investigated. The reflectance amplitude was measured and the reflectance coefficients were calculated for six uniform sediments with different grain sizes ranging from 0.1–0.3 to 2.0–2.5 mm. The scattering intensity of the six sediments with a uniform grain size distribution at the same measurement distance varies to some extent. There is variation in the intensity of acoustic wave reflections for different grain sizes, but some of the differences are not statistically significant. The dispersion coefficients of the acoustic reflection intensities for all sediments, except for those with a grain size of 1.0–1.5 mm, are less than 5% at different measurement distances. These coefficients are almost independent of the detection distance.

The role of wave-induced mixing in spring phytoplankton bloom in the South Yellow Sea - Xuehai Liu; Xinming Pu; Dapeng Qu; Zongjun Xu (Marine Pollution Bulletin, 2025)

Sediment classification in the paleo-oceanic environment based on multi-acoustic reflectance characteristics in the Southern Tianshan Mountains - Huancheng Zhen; Xinghui Cao; Zhiguo Qu; Dapeng Zou; Shuai Xiong; Jiang Song; Hao Guo (Frontiers in Marine Science, 2024)
The grain size of sediments is a crucial parameter in sedimentology, with significant implications for submarine engineering and water conservancy projects. In this study, we developed an acoustic reflection measurement system using a self-developed, high-precision, high-frequency shallow stratigraphic profiler. The system's accuracy was validated with standard acrylic samples. Results showed that within the sediment grain size range of 0.3 to 2.5 mm, the acoustic reflection amplitude increased with grain size. However, distinguishing grain sizes between 0.1 and 0.3 mm from those between 1.0 and 1.5 mm based solely on reflection amplitude proved challenging. Notably, the differences in wavefront flare shapes between these grain sizes were readily apparent. Therefore, combining reflection peak amplitude with time-domain waveform analysis enables more precise sediment grain size classification.

Current observation and analysis based on mooring systems in the Andaman Sea - Yimeng Wang; Jingsong Guo; Dapeng Qu; Zhixin Zhang; Chalermrat Sangmanee; Varintha Vasinamekhin; Binghuo Guo (Journal of Oceanology and Limnology, 2024)

Electroacoustic performance online measurement under extreme pressure using an 11,000-m transceiver - Zhiguo Qu; Zhi Zhong; Dapeng Zou; Xinghui Cao; Mingguang Shan; Yongqiang Xie; Hui Cheng (Marine Georesources & Geotechnology, 2023)

Calibration and application of high-frequency submersible sub-bottom profiler for deep-sea surficial sediment measurement - Xinghui Cao; Dapeng Zou; Zhiguo Qu; Huancheng Zhen; Hui Cheng; Zhiyi Wei (Marine Georesources & Geotechnology, 2023)

Visible-light-driven photocatalytic degradation of tetracycline hydrochloride by Z-scheme Ag3PO4/1T@2H-MoS2 heterojunction: Degradation mechanism, toxicity assessment, and potential applications - Xiuyi Hua; Haijun Chen; Chang Rong; Francis Addison; Deming Dong; Jiao Qu; Dapeng Liang; Zhiyong Guo; Na Zheng; Haiyang Liu (Journal of Hazardous Materials, 2023)

Measuring the sound speed in deep-sea first sediment layer using a high-frequency submersible sub-bottom profiler: Method and sea trial application - Zhiguo Qu; Dapeng Zou; Mingguang Shan; Xinghui Cao; Yongqiang Xie (Marine Georesources & Geotechnology, 2022)

Recognition on the forming-vanishing process and underlying mechanisms of the hypoxia off the Yangtze River estuary - QinSheng Wei; BaoDong Wang; JianFang Chen; ChangShui Xia; DaPeng Qu; LinPing Xie (Science China Earth Sciences, 2015)

HGF inhibits TGF-β1-induced myofibroblast differentiation and ECM deposition via MMP-2 in Achilles tendon in rat - Qingbo Cui; Zhigang Wang; Dapeng Jiang; Lihui Qu; Junbin Guo; Zhaozhu Li (European Journal of Applied Physiology, 2011)